Symmetric and dipolar electromagnetic waves in coaxial structure filled by non-uniform dissipative plasma with azimuth magnetic field - Olefir, V.P.; Sporov, A.E. (Вопросы атомной науки и техники, 2011)
The aim of this report is the investigation of influence of effective collision rate, the value of direct current that
flows along the central conductor of the waveguide structure, waveguide geometric parameters and plasma density
radial profile on the dispersion, spatial attenuation and radial wave field structure of high-frequency electromagnetic
waves. It was shown that mentioned parameters can be used for effective control of the dispersion and attenuation of the
studied waves. Наведено дослідження впливу ефективної частоти зіткнень електронів, сили постійного струму, що протікає
по центральному провіднику коаксіальної хвилеводної структури, геометричних параметрів хвилеводу та
радіального профілю густини плазми на дисперсію, просторове загасання та радіальну структуру поля
високочастотних електромагнітних хвиль. Показано, що, змінюючи вказані параметри, можливо ефективно
керувати дисперсійними характеристиками та просторовим загасанням хвиль, що розглядаються. Приведено исследование влияния эффективной частоты столкновений электронов, силы постоянного тока,
протекающего по центральному проводнику коаксиальной волноводной структуры, геометрических
параметров волновода и радиального профиля плотности плазмы на дисперсию, пространственное затухание и
радиальную структуру поля высокочастотных электромагнитных волн. Показано, что, изменяя указанные
параметры, можно эффективно управлять дисперсионными характеристиками и коэффициентом
пространственного затухания рассматриваемых волн.